John Maynard Keynes of Bloomsbury: Four short talks - Craufurd D. W. Goodwin; E. Roy Weintraub; Kevin D. Hoover; Bruce Caldwell (Duke University, Center for the History of Political Economy (CHOPE), 2009)
Four talks on Keynes in relation to the Bloomsbury Group: I. Maynard Keynes of Bloomsbury (Craufurd Goodwin); II. Keynes as Policy Advisor (E. Roy Weintraub); III. Keynes and Economics (Kevin D. Hoover); IV. Keynes and Hayek (Bruce Caldwell). The talks were delivered as part of roundtable discussion on John Maynard Keynes of Bloomsbury, the inaugural event of the Center for the History of Political Economy at Duke University, and were held in conjunction with Vision and Design: A Year of Bloomsbury, a campus-wide interdisciplinary program surrounding an exhibition of Bloomsbury art at Duke University's Nasher Museum of Art.
Keywords: B20; B22; B31; B25; 330; John Maynard Keynes; Bloomsbury Group; economic policy; Great Depression; macroeconomics; Friedrich A. von Hayek; Keynesian economics; Austrian economics